Expansins and Internodal Growth of Deepwater Rice. - Cho, H. T. (1997)
The distribution and activity of the cell wall-loosening protein expansin is correlated with internodal growth in deepwater rice (Oryza sativa L.). Acid-induced extension of native cell walls and reconstituted extension of boiled cell walls were confined to the growing region of the internode, i.e. to the intercalary meristem (IM) and the elongation zone. Immunolocalization by tissue printing and immunoblot analysis, using antibody against cucumber expansin 29 as a probe, confirmed that rice expansin occurred primarily in the IM and elongation zone. Rice expansin was localized mainly around the vascular bundles at the base of the IM and along the inner epidermal cell layer surrounding the internodal cavity. Submergence greatly promoted the growth of rice internodes, and cell walls of submerged internodes extended much more in response to acidification than did the cell walls of air-grown internodes. Susceptibility of cell walls to added expansin was also increased in submerged internodes, and analysis by immunoblotting showed that cell walls of submerged internodes contained more expansin than did cell walls of air-grown internodes. Based on these data, we propose that expansin is involved in mediating rapid internodal elongation in submerged deepwater rice internodes.